Leadership trends among orthopaedic trauma surgery fellowship directors: a cross-sectional demographic review. Issue 2 (13th March 2021) - Sama, Andrew J.; Schiller, Nicholas C.; Ramirez, Cody M.; Yong, Taylor M.; Donnally, Chester J.; Spielman, Amanda F.; Gitajn, Ida L.; Dodds, Seth D.; Quinnan, Stephen M.
Abstract : Background: Fellowship directors in orthopaedic trauma surgery have an immense impact on the current and future trainees within orthopaedics. The purpose of our study was to evaluate and better understand the characteristics that are shared among current orthopaedic trauma surgery fellowship directors to provide a framework for aspiring leaders and to present a demographic snapshot. Methods: Orthopaedic trauma fellowship programs were identified using the Orthopaedic Trauma Association Directory for 2019 to 2020. Data for each fellowship director was gathered via online review, email, telephone, and curriculum vitae collection. Results: Demographic information was gathered for 72 fellowship directors. Of these, 93% of the leadership was male. Additionally, 40 (55%) fellowship directors responded to the racial classification question. Of those responding, 37 identified as Caucasian, one as Asian-American, one as Hispanic/Latino, and one as African American. The mean age of the current fellowship directors (51.4 yr), h-index (15.1), year of residency (2001) and fellowship (2003) graduation, time of employment at current institution (13.8 yr), time since training until fellowship director appointment (9.8 yr) were analyzed. The top residency and fellowship programs that produced future fellowship directors were University of Pittsburgh (n=4) and Harborview Medical Center (n=17). Conclusions: Our investigation highlighted the qualifications of orthopaedic trauma fellowship directors and can guide future leaders. A select few institutions train a disproportionate share of the current fellowship directors. Gender and racial diversity are limited in this population of leaders. Level of Evidence: Level III.